The history of the glomus tumors -- nonchromaffim chemodectoma: a glimpse of biomedical Camelot. - Ruben RJ (Acta Oto-Laryngologica, 2007)
Conclusions: Guild's initial 231 word report was the source of a stream of positive consequences; the glomus story is a paradigm of the utility of basic science. Background: The glomus tumor has had a number of different names, including glomus jugulare, glomus tympanicum, nonchromaffin paraganglioma, and carotid body tumor. Although they have occurred throughout the ages, glomus tumors were neither recognized nor understood until Harry Rosenwasser read Stacy Guild's report of 1941. Materials and methods: The pertinent literature from the 18th century to the present was reviewed. Results: Stacy Guild's pursuit of basic scientific knowledge laid the foundation for a chain of clinical and scientific advances that continue to the present and will continue to have positive effects into the future. Guild's brief basic science note of 1941 was used through the scholarship of Rosenwasser to define a clinical entity that had not been recognized. This new nosology, rapidly adopted worldwide, provided a biological basis for the rational grouping of patients and analysis of their ills. Subsequent to this, it was noted that many of these tumors occurred in families, apparently transmitted as an autosomal dominate but occurring primarily in the males. Further study based on these observations led to the identification of a genetic mechanism of inheritance: genomic imprinting. A further advance of the synergetic relationship between the environment - oxygen tension/altitude - and the mutation explains Guild's 1953 observations that all patients, without any sexual predominance, have glomus bodies but not all have tumors.